Academe in transition: Transformations in the Polish academic profession - Kwiek, Marek (My University, 2003)
The period since 1989 has been an extremely dynamic one in Polish higher education. New opportunities have opened up for the academic community, along with new challenges. Suddenly, the academic profession has arrived at a stage that combines far-reaching autonomy with rather uncertain individual career prospects. In recent years, a number of new laws have been proposed that were intended to change the whole structure of recruitment, promotions, remuneration, working conditions, and appointments of academic faculty. All this has occurred admidst the strains and tensions resulting from changes in the broader society. The sudden passage from the more or less elite higher education system to mass higher education with a strong and dynamic private sector has transformed the situation of the academic community beyond all recognition. The transition has resulted in a new set of values and changes in position, tasks, and roles for academe in society. Today, the future of the Polish academic profession remains undetermined. The positive changes were accompanied by the chronic underfunding of public higher education. Polish academics have learned to accommodate themselves to the permanent state of uncertainty in which they are forced to operate. The present paper analyzes the current situation from the perspective of global changes affecting the academic profession.
Keywords: academic profession; higher education reforms in Central and Eastern Europe; Central and Eastern Europe; Poland; the state and the market; Polish reforms; prolerianisation; chronic underfunding; postcommunist higher education; resource-poor systems